TRUCKS - Press the button to hear the horn honk! - Dorling Kindersley, Inc.; Landis, Beth, editor (DK PUBLISHING, INC.,Dorling Kindersley New York, 2002)
Realistic sounds of both trucks make this book jump to life! Loaded with superb full-color photography, elementary text, and sounds to accompany each story, this easy-to-hold board book is sure to provide hours of fun to delight and entertain preschool children. Push the button and hear the horn of a big rig, then look inside and learn more. In Trucks, stories come to life when children listen and read at the same time.
A hardcover board book with sound buttons featuring labelled photographs of trucks. Pressing each button plays a related truck sound. Designed for toddlers and preschoolers.
ages 1-4.
Text in English.
Keywords: Trucks -- Juvenile literature, Board books